2016
DOI: 10.1109/jphotov.2016.2583790
|View full text |Cite
|
Sign up to set email alerts
|

An Illumination- and Temperature-Dependent Analytical Model for Copper Indium Gallium Diselenide (CIGS) Solar Cells

Abstract: In this paper, we present a physics-based analytical model for CIGS solar cells that describes the illumination-and temperature-dependent current-voltage (I-V) characteristics and accounts for the statistical shunt variation of each cell. The model is derived by solving the drift-diffusion transport equation so that its parameters are physical, and, therefore, can be obtained from independent characterization experiments. The model is validated against CIGS I-V characteristics as a function of temperature and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…3,4 It was recently shown that in analogy to organic-and amorphous silicon-based devices, the non-linear shunt in CIGS solar cells is best described by the SCLC (space-chargelimited current) theory. 1,2,[4][5][6] The basic model suggests the presence of a dielectric layer embedded between two injecting contacts, which provide only one type of carrier, while the other type of carrier is blocked. 7 It was thereby proposed that CIGS-based devices contain an intrinsic layer located in the CIGS absorber, which is formed due to some undefined electronic non-uniformity of the absorber.…”
mentioning
confidence: 99%
“…3,4 It was recently shown that in analogy to organic-and amorphous silicon-based devices, the non-linear shunt in CIGS solar cells is best described by the SCLC (space-chargelimited current) theory. 1,2,[4][5][6] The basic model suggests the presence of a dielectric layer embedded between two injecting contacts, which provide only one type of carrier, while the other type of carrier is blocked. 7 It was thereby proposed that CIGS-based devices contain an intrinsic layer located in the CIGS absorber, which is formed due to some undefined electronic non-uniformity of the absorber.…”
mentioning
confidence: 99%
“…First, because the conventional single‐diode and double‐diode models cannot capture the physics of thin‐film solar cells (eg, voltage‐dependent photocurrent), one needs to adopt new circuit models. Sun et al, Sun et al, Sun et al, and Crandall developed a set of physics‐based circuit models for a‐Si, perovskite, CIGS, and CdTe solar cells. These models also contain physical parameters pertaining to degradation pathways unique to these thin‐film technologies, eg, s f and s b in Sun et al can describe the interface degradation in a perovskite solar cell .…”
Section: Discussionmentioning
confidence: 99%
“…Mainstream PV technologies can be categorized into 3 groups: (1) p‐n homojunction (eg, c‐Si and GaAs), (2) p‐i‐n junction (eg, a‐Si and perovskites), and (3) p‐n heterojunction (eg, CIGS and CdTe). Depending on a particular technology, we select the corresponding equivalent circuit in the Suns‐Vmp method: for example, Sun et al for CIGS, Sun et al for perovskites, and Chavali for silicon heterojunction. Because a solar cell is exposed to varying illumination intensities and temperatures, the equivalent circuit must be capable of describing the illumination‐dependent and temperature‐dependent IV curves.…”
Section: The Suns‐vmp Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lognormal distribution of shunt can be inherent in thin-film technologies, which originated from the fact that grain size in poly-crystalline films is lognormal distributed regardless of the choice of materials. Using the physics-based module simulation framework [19][20], we performed Monte Carlo simulation for CIGS modules with different sizes given a lognormal distribution of shunt to investigate the effect of module area on the efficiency (Figure 10). One important observation from the simulation is that modules with a larger size have a narrower distribution of efficiency (i.e., smaller variance).…”
Section: Potential Effect Of Increased Module Size On Energy Yieldmentioning
confidence: 99%